2021
DOI: 10.1136/bmjpo-2021-001206
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions of leukotriene receptor antagonists in children with asthma: a systematic review

Abstract: BackgroundAsthma is the most common chronic condition of childhood. Leukotriene receptor antagonists (LTRAs) are included in international guidelines for children and young people (CYP), but there have been highly publicised concerns about potential adverse effects. The aim was to identify and understand the reported frequency of adverse drug reactions (ADRs) attributed to LTRAs in CYP with asthma.MethodsEmbase, MEDLINE, PubMed and CINAHL were searched up to October 2020. Reference lists of eligible papers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
7
0
3
Order By: Relevance
“…21 22 Since then, further concerns regarding the adverse drug reactions attributed to montelukast in CYP with asthma have been outlined in a recent PROSPERO systematic review. 23 …”
Section: Discussionmentioning
confidence: 99%
“…21 22 Since then, further concerns regarding the adverse drug reactions attributed to montelukast in CYP with asthma have been outlined in a recent PROSPERO systematic review. 23 …”
Section: Discussionmentioning
confidence: 99%
“…They remarked that the side effects associated with LTRAs are predominantly gastrointestinal and neuropsychiatric disorders. 18 In the literature, there are few cases of montelukast-associated hallucinations. [19][20][21] In 2015, Erdem et al 21 reported 4 hallucinations in 1024 cases.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Przyjmowanie leków przeciwleukotrienowych może skutkować występowaniem łagodnych działań niepożądanych, natomiast poważniejsze działania niepożądane występują u bardzo niewielkiego odsetka pacjentów (Tabela 10). Wobec tego terapia z wykorzystaniem LTRA jest bezpieczna zarówno u dorosłych i u dzieci [33,42,45,157,158]. W ostatnim czasie pojawiły się doniesienia na temat dużo wyższego niż dotąd sądzono przenikania LTRA, zwłaszcza montelukatu, przez barierę krew-mózg, [158].…”
Section: Działania Niepożądane Leków Przeciwleukotrienowychunclassified
“…Wobec tego terapia z wykorzystaniem LTRA jest bezpieczna zarówno u dorosłych i u dzieci [33,42,45,157,158]. W ostatnim czasie pojawiły się doniesienia na temat dużo wyższego niż dotąd sądzono przenikania LTRA, zwłaszcza montelukatu, przez barierę krew-mózg, [158]. Fakt ten wiąże stosowanie montelukastu z zaburzeniami psychiatrycznymi prowadzącymi do myśli samobójczych oraz zespołem Churga-Straussa (przewlekłym alergicznym zapaleniem naczyń krwionośnych) [95,150,158,159].…”
Section: Działania Niepożądane Leków Przeciwleukotrienowychunclassified
See 1 more Smart Citation